2015
DOI: 10.5194/acp-15-9501-2015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the contribution of long-range transport to particulate matter (PM) mass loadings at a suburban site in the north-western Indo-Gangetic Plain (NW-IGP)

Abstract: Abstract. Many sites in the densely populated Indo-Gangetic Plain (IGP) frequently exceed the national ambient air quality standard (NAAQS) of 100 μg m−3 for 24 h average PM10 and 60 μg m−3 for 24 h average PM2.5 mass loadings, exposing residents to hazardous levels of particulate matter (PM) throughout the year. We quantify the contribution of long-range transport to elevated PM levels and the number of exceedance events through a back-trajectory climatology analysis of air masses arriving at the IISER Mohal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 64 publications
(62 reference statements)
3
34
1
Order By: Relevance
“…Distinctive to the IGP were high OA : BC ratios (10-15), which are somewhat higher than for similar polluted environments such as China during summer with a ratio of ∼ 4 (Ho et al, 2006;Ni et al, 2018). It has been indicated that OA : BC ratios over India could be greater than expected due to the dominance of biomass burning rather than fossil fuel emissions, with the highest values in the pre-monsoon season (Ram and Sarin, 2011;Bisht et al, 2015;Kumar and Yadav, 2016) as seen in our data. Outside the IGP, the aerosol species concentrations are consistent with the aerosol sources, with more informal industries and manufacturing industries present that form high concentrations of SO 4 aerosol through the conversion of sulfur dioxide (SO 2 ) into sulfuric acid (H 2 SO 4 ).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Distinctive to the IGP were high OA : BC ratios (10-15), which are somewhat higher than for similar polluted environments such as China during summer with a ratio of ∼ 4 (Ho et al, 2006;Ni et al, 2018). It has been indicated that OA : BC ratios over India could be greater than expected due to the dominance of biomass burning rather than fossil fuel emissions, with the highest values in the pre-monsoon season (Ram and Sarin, 2011;Bisht et al, 2015;Kumar and Yadav, 2016) as seen in our data. Outside the IGP, the aerosol species concentrations are consistent with the aerosol sources, with more informal industries and manufacturing industries present that form high concentrations of SO 4 aerosol through the conversion of sulfur dioxide (SO 2 ) into sulfuric acid (H 2 SO 4 ).…”
Section: Discussioncontrasting
confidence: 44%
“…The diverse living habits, fuel and land use make understanding the complexity of emissions and atmospheric dynamics challenging. The Indo-Gangetic Plain (IGP) in the Indian sub-continent is one such polluted region in South Asia; its unique geomorphology, meteorology and characteristic variations in aerosol particles have drawn the attention of aerosol researchers for many years (Pawar et al, 2015;Singh et al, 2017). Aerosol mass sources within the IGP are mostly dominated by natural sources such as dust, but also anthropogenic emissions associated with traffic, biomass burning, waste incineration, and crop and wood burning (Banerjee et al, 2015;Singh et al, 2017), with Delhi being one of the most polluted locations (Sharma et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar publicly available network surface ozone measurements are not available for India and China during this time period. We also compare ozone and PM surface observations from a site at the Indian Institute of Science Education and Research (IISER) Mohali in Chandigarh, India provided by Sinha et al (2015) and Pawar et al (2015), respectively, with simulated concentrations from GEOS-Chem (Fig. 3).…”
Section: Evaluation With Observationsmentioning
confidence: 99%
“…Understanding, identifying and characterising air pollution sources and their effect on local and regional areas, is important for health impact studies as well as radiative forcing assessments on local and global scales (Lawrence et al, 2007). The Indo-Gangetic Plain (IGP) in northern India is one such polluted region in south Asia (Pawar et al, 2015;Singh et al, 2017). Aerosol mass sources within the IGP are dominated by natural sources such as dust, but also anthropogenic emissions associated with traffic, biomass burning, waste incineration and crop and wood burning (Banerjee et al, 2015;Singh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%